Influence of Seaweed Liquid Fertilizer on the Growth and Biochemical Composition of Legume Crop, Cajanus cajan (L.) Mill sp. - and S. Geetha2, B. Sathya1, H. Indu1, R. Seenivasan1* (Journal of Phytology, 2010)
Seaweed or benthic marine algae are the group of plants that live either in marine or brackish water environment. Like the land plants seaweed contains photosynthetic pigments and with the help of sunlight and nutrient present in the seawater, they photosynthesize and produce food. Seaweeds are found in the coastal region between high tide to low tide and in the sub-tidal region up to a depth where 0.01 % photosynthetic light is available. The application of seaweed fertilizer for different crop was of great importance to substitute the commercial chemical fertilizers and to reduce the cost of production. Liquid fertilizers derived from seaweeds are found to be superior to chemical fertilizers due to high level of organic matter, micro and macro elements, vitamins and fatty acids and also rich in growth regulators. In the present study the effect of seaweed liquid fertilizer prepared from different seaweeds Grateloupia lithophila (Red algae), Chaetomorpha linum (Green Algae), Sargassum wightii (Brown algae) at different concentrations (10%, 20%, 30%, 40%, 50%, 100%)Â  on the plant Cajanus cajan were studied. At 30% concentration the SLF prepared from Chaetomorpha linum showed maximum growth parameters on Cajanus cajan. Similarly SLF of Sargassum wightii promoted maximum photosynthetic pigments and biochemical parameters at 20% concentration than the control.Â  Among the three seaweeds used Sargassum wightii and Chaetomorpha linum showed better results than the Grateloupia lithophila at lower concentration. (SLF- Seaweed Liquid Fertilizer).